Novel insights into the role of acetyl-CoA producing enzymes in epigenetic regulation - Russo, Marta; Pileri, Francesco; Ghisletti, Serena (Frontiers in Endocrinology, 2023)
Inflammation-dependent changes in gene expression programs in innate immune cells, such as macrophages, involve extensive reprogramming of metabolism. This reprogramming is essential for the production of metabolites required for chromatin modifications, such as Acetyl-CoA, and regulate their usage and availability impacting the macrophage epigenome. One of the most transcriptionally induced proinflammatory mediator is nitric oxide (NO), which has been shown to inhibit key metabolic enzymes involved in the production of these metabolites. Recent evidence indicates that NO inhibits mitochondrial enzymes such as pyruvate dehydrogenase (PDH) in macrophages induced by inflammatory stimulus. PDH is involved in the production of Acetyl-CoA, which is essential for chromatin modifications in the nucleus, such as histone acetylation. In addition, Acetyl-CoA levels in inflamed macrophages are regulated by ATP citrate lyase (ACLY) and citrate transporter SLC25A1. Interestingly, Acetyl-CoA producing enzymes, such as PDH and ACLY, have also been reported to be present in the nucleus and to support the local generation of cofactors such as acetyl-CoA. Here, we will discuss the mechanisms involved in the regulation of Acetyl-CoA production by metabolic enzymes, their inhibition by prolonged exposure to inflammation stimuli, their involvement in dynamic inflammatory expression changes and how these emerging findings could have significant implications for the design of novel therapeutic approaches.